(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of studies carried out with blood-sucking mosquitoes of the genus Anopheles, indicates the places of their distribution and characteristic features on the example of the Surkhandarya region. The research results show that in our collections An. superpictus is rarely found with An. pulcherrimus, and An. hurcanus did not come across at all. Larvae of An. pulcherrimus and An. hurcanus. The number of mosquitoes at daytime in nature and in settlements depends on the size of the mosquito population, on the location of the daytime and larval biotope, as well as on the relative humidity and air temperature in places of the daytime.